2014
DOI: 10.1055/s-0034-1390700
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metal stents for obstructing colonic and extracolonic cancer: European Society of Gastrointestinal Endoscopy (ESGE) Clinical Guideline

Abstract: This Guideline is an official statement of the European Society of Gastrointestinal Endoscopy (ESGE). This Guideline was also reviewed and endorsed by the Governing Board of the American Society for Gastrointestinal Endoscopy (ASGE). The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was adopted to define the strength of recommendations and the quality of evidence. Main recommendations The following recommendations should only be applied after a thorough diagnostic evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
270
2
30

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(305 citation statements)
references
References 75 publications
(164 reference statements)
3
270
2
30
Order By: Relevance
“…In patients presenting with (sub)total obstruction due to a left-sided (descending) tumour, temporary pre-operative stenting can be considered to reduce perioperative morbidity and risks of surgery, but the risk of perforation must be considered 151,152,168 . Colostomy versus stent for palliation could be considered in patients presenting with obstruction and multiple distant metastases 151,152,169 .…”
Section: Managementmentioning
confidence: 99%
“…In patients presenting with (sub)total obstruction due to a left-sided (descending) tumour, temporary pre-operative stenting can be considered to reduce perioperative morbidity and risks of surgery, but the risk of perforation must be considered 151,152,168 . Colostomy versus stent for palliation could be considered in patients presenting with obstruction and multiple distant metastases 151,152,169 .…”
Section: Managementmentioning
confidence: 99%
“…In addition to a possibly high complication rate, questions have been raised about the oncologic long-term results following stent placement, since it is thought that tumor manipulation by stent placement possibly leads to micro-perforations and tumor spill. However, only a few studies have reported on long-term outcomes (Erichsen et al 2015; Sloothaak et al 2014), a recent systematic review recommended stent placement in only palliative and unfit patients, which is in accordance with the most recent ESGE Guideline (van Hooft et al 2014; Zhoa et al 2014; Frago et al 2014). ESGE guideline states that colonic self-expandable metal stent (SEMS) placement as a bridge to elective surgery is not recommended as a standard treatment of symptomatic left-sided malignant colonic obstruction and for patients with potentially curable but obstructing left-sided colonic cancer, stent placement may be considered as an alternative to emergency surgery in those who have an increased risk of postoperative mortality, i.e.…”
Section: Discussionmentioning
confidence: 85%
“…TDT placement is the first choice for left‐sided malignant colonic obstruction in our department because postoperative long‐term survival is thought to be one of the most essentially important outcomes, and the long‐term oncological outcome of SEMS placement is controversial. The European Society of Gastrointestinal Endoscopy does not recommend the use of a SEMS as a bridge to elective surgery for standard treatment of potentially curable patients with left‐sided malignant colonic obstruction 23. Overall, elective one‐stage resection and anastomosis for stage IV cancer are controversial from the viewpoint of future chemotherapy; however, we believe that decompression with a TDT is a valuable option for the management of malignant left‐sided colorectal obstruction.…”
Section: Discussionmentioning
confidence: 98%